2020
DOI: 10.3390/ijms21197220
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Internalization of Nanoparticles Following Ionizing Radiation Leads to Mitotic Catastrophe in MG-63 Human Osteosarcoma Cells

Abstract: This study aims to investigate whether ionizing radiation combined with doxorubicin-conjugated iron oxide nanoparticles (NP-DOX) improves the internalization and cytotoxic effects of the nano-carrier-mediated drug delivery in MG-63 human osteosarcoma cells. NP-DOX was designed and synthesized using the co-precipitation method. Highly stable and crystalline nanoparticles conjugated with DOX were internalized in MG-63 cells through macropinocytosis and located in the perinuclear area. Higher nanoparticles intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Six specific diffraction planes corresponding to 2θ values of ~30, ~35, ~43, ~53, ~57 and ~62 (°) were thus identified, namely (2 2 0), (3 1 1), (4 0 0), (4 2 2), (5 1 1) and (4 4 0). The results are in concordance with previously reported data [83,84] on crystalline magnetite with a spinel cubic structure. The IR spectrum from Figure 2 demonstrates the successful conjugation of EG molecules onto Fe3O4 particles.…”
Section: Resultssupporting
confidence: 94%
“…Six specific diffraction planes corresponding to 2θ values of ~30, ~35, ~43, ~53, ~57 and ~62 (°) were thus identified, namely (2 2 0), (3 1 1), (4 0 0), (4 2 2), (5 1 1) and (4 4 0). The results are in concordance with previously reported data [83,84] on crystalline magnetite with a spinel cubic structure. The IR spectrum from Figure 2 demonstrates the successful conjugation of EG molecules onto Fe3O4 particles.…”
Section: Resultssupporting
confidence: 94%
“…Results of the performed experiment with osteosarcoma cell lines showed that parthenolide, an NF-κB signaling inhibitor, acted synergistically with RT, providing a significant reduction of the number of viable cancer cells in the analyzed samples. Other radiosensitizers are under investigation [33].…”
Section: Discussionmentioning
confidence: 99%
“…17 Nanoparticle in cancer therapy has been evaluated in the majority of solid tumors. Interesting examples to note, published the last year, are doxorubicin conjugated iron oxide particles in osteosarcoma, 18 and the role ionizing radiation plays in the internalization and cytotoxic effects of the nano-carrier mediated drug delivery, mannose modified cyclodextrin with regorafenib in colorectal cancer to attenuate inflammation and inhibit tumor associated macrophage activation by targeting macrophages whilst improving regorafenib's anti-tumor effect by potentiating k i n a s e s u p p r e s s i o n , 19 c o m b i n a t i o n c h e m ophotodynamic therapy using lipid encapsulated polymeric nanoparticles against platinum resistant ovarian carcinoma cells, Yang et al, the use of lipid polymer hybrid nanoparticles constructed for CRISPR/CAS9 plasmids targeting drug resistant glioblastoma, 20 sorafenib nanoparticles as targeted ferroptosis-induced treatment of hepatocellular carcinoma, 21 and photothermal therapy and radiosensitization using silver nanoparticles in triple negative breast cancer without affecting nonmalignant mammary epithelial cells are some compelling examples. 22 The use of cancer theranostics combine anticancer targeted therapy and diagnosis by nanocarriers which contain therapeutic and imaging agents allow the selective detection of cancerous cells and their visualization through real time imagine techniques.…”
Section: Nanotechnology and Nanomedicine In Oncologymentioning
confidence: 99%